2020
DOI: 10.21273/hortsci14396-19
|View full text |Cite
|
Sign up to set email alerts
|

Sand Size Affects Topdressing Removed by Mowing and Anthracnose on Annual Bluegrass Putting Green Turf

Abstract: Sand size can affect the ability to incorporate topdressing into the turf canopy and thatch on golf course putting greens; unincorporated sand interferes with mowing and play. This 3-year field trial was initiated to determine the effects of sand size on sand incorporation, surface wetness, and anthracnose (caused by Colletotrichum cereale Manns sensu lato Crouch, Clarke, and Hillman) of annual bluegrass [Poa annua L. f. reptans Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Although, fairways topdressed with a finer sand sometimes retained more moisture compared to medium-coarse or coarse sand, VWC of the fine sand treatment was similar or lower than the non-topdressed control (Henderson & Miller, 2009). Plots topdressed with medium-fine sand did not retain more water than the non-topdressed plots in the current study, similar to the findings of others (Henderson & Miller, 2009;Wang et al, 2020).…”
Section: Volumetric Water Content and Infiltrationsupporting
confidence: 92%
See 3 more Smart Citations
“…Although, fairways topdressed with a finer sand sometimes retained more moisture compared to medium-coarse or coarse sand, VWC of the fine sand treatment was similar or lower than the non-topdressed control (Henderson & Miller, 2009). Plots topdressed with medium-fine sand did not retain more water than the non-topdressed plots in the current study, similar to the findings of others (Henderson & Miller, 2009;Wang et al, 2020).…”
Section: Volumetric Water Content and Infiltrationsupporting
confidence: 92%
“…We found that a greater rate (0.3 L m −2 ) of medium‐fine sand can be applied without a substantial increase in the quantity of sand removed by mowing. Coarse (0.5–1.0 mm) and very coarse (1.0–2.0 mm) sand particles are more likely to be removed by mowing than particles <0.5 mm in diameter (Stier & Hollman, 2003; Taylor, 1986; Wang et al., 2020). In our study, medium‐fine sand did not contain particles above 0.5 mm (Table 1); therefore, substantially less sand would be expected to be removed by mowing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diameter of soil cores used for OM analysis and the number of samples collected per plot vary greatly in the turfgrass literature. Most of these studies collected between two and five soil samples per plot (Barton et al, 2009;Carrow et al, 1987;Dunn et al, 1995;Espevig et al, 2012;Fu et al, 2009;McCarty et al, 2005;Murphy et al, 1993;Schmid et al, 2014;Stier and Hollman, 2003;Wang, 2015). Kauffman et al (2013) conducted a field trial in which they investigated the effect of sample size (number per plot) on thatch/mat depth and OM content of four warmseason grasses.…”
Section: Monitoring and Measuring Organic Matter In Turfgrassmentioning
confidence: 99%